Auditoría de gestión al cuerpo de bomberos de la ciudad de Latacunga, provincia de Cotopaxi, durante el período enero – diciembre de 2013. - Canga Cevallos, Ana Cristina (2015)
The application of management audit to the Fire Department of Latacunga, will measure the degree of compliance with the goals, objectives and policies established by the same in terms of efficiency, effectiveness, economy, equity, quality, ecology, ethics and impact , which will help the performance of resources: human, financial, material and technological, established by management and implemented in all departments for timely decisions. All of them provide the administration determining anomalies, deviations and errors, of which the recommendations are based to contribute to continuous improvement, clarifying the actual results of the steps taken in proceedings for the institution. Deductive method, the statistical method, the analytical method and the same interview instrument that facilitated the collection at source of information that strengthened the basis for further analysis: certain research methodologies used, including for its execution and interpretation. The audit is reflected through the issuance of the final report, communicating the findings referring to the flaws and irregularities, for which the audit disclosed the Administrative Council a useful and timely report that enables it to make recommendations to achieve internal improvements